Change in Area, Production and Productivity of Rice, Wheat and Pulses Through National Food Security Mission (NFSM) (Indian Journal of Extension Education, 2017)
National Food Security Mission (NFSM) has been launched from 2007-08 to increase the area, production and productivity of rice, wheat and pulses. The study was undertaken to conduct trend analysis of change in area, production and productivity of rice, wheat and pulses through National Food Security Mission. To carry out the trend analysis, the growth in the area, production and productivity of rice, wheat and pulses in Uttar Pradesh was estimated using the compound growth function. The necessary secondary data were collected for a period of 6 years from 2007-08 to 2012-13 for rice and wheat and for pulse a period of five years data from 2007-08 to 2011-12 was used. The results of the study have shown that area under rice, wheat and pulses increased with compound growth rate of 7.81, 1.85, and 3.48 percent respectively. The growth in production of rice, wheat and pulses was 3.57, 3.46, and 9.11 percent respectively. Similarly productivity growth of rice, wheat and pulses was 3.55, 2.99 and 4.73 percent respectively. The growth in production and productivity of wheat was found to be significant. Similarly, the productivity of rice and production of pulse was found to be significant.